2019
DOI: 10.3390/ijms20184495
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Chaperone DNAJB6, but Not DNAJB1, Suppresses the Seeded Aggregation of Alpha-Synuclein in Cells

Abstract: Alpha-synuclein (α-Syn) can misfold and aggregate, causing the degeneration of dopaminergic neurons, as seen in Parkinson’s disease (PD). We recently demonstrated that DNAJB6, a co-chaperone found in Lewy bodies (LB), suppresses the aggregation of α-Syn in cells and in vitro. In this study, we compared the capacities of DNAJB1 and DNAJB6 to suppress the seeded α-Syn aggregation in HEK293 cells expressing α-Syn tagged with cyan fluorescent protein (CFP) or yellow fluorescent protein (YFP). The aggregation of α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 42 publications
3
23
3
Order By: Relevance
“…The antiaggregation effect of DNAJB6b on α-synuclein in cells and in vitro was shown to be HSPAand JD-dependent and largely independent of the hydroxyl groups of the S/T region [61]. Very recently, further studies confirmed the increased susceptibility of DNAJB6-deficient cells to seeded α-synuclein aggregation and suggested that DNAJB6 promotes proteasomal turnover of α-synuclein [52].…”
Section: Antiaggregation and Cytoprotectionmentioning
confidence: 93%
See 1 more Smart Citation
“…The antiaggregation effect of DNAJB6b on α-synuclein in cells and in vitro was shown to be HSPAand JD-dependent and largely independent of the hydroxyl groups of the S/T region [61]. Very recently, further studies confirmed the increased susceptibility of DNAJB6-deficient cells to seeded α-synuclein aggregation and suggested that DNAJB6 promotes proteasomal turnover of α-synuclein [52].…”
Section: Antiaggregation and Cytoprotectionmentioning
confidence: 93%
“…Interactions with other BAG proteins in addition to BAG3 [2] are compatible with the idea that DNAJB6 has cochaperone functions related to multiple pathways. Some experimental evidence indicates that DNAJB6 may promote proteasomal degradation of clients [30,52], and this is supported by its interaction with the proteasome subunit PSMD2 [2].…”
Section: Cochaperone Functionmentioning
confidence: 99%
“…Several DNAJ proteins are linked to PD, and a role for DNAJB6, a member of this family in the suppression of α-synuclein aggregation and proteasomal degradation, has been reported [ 83 ]. Knockout of DNAJB6 in HEK239 cells resulted in increased aggregation of α-synuclein [ 83 ]. Interestingly, this induced aggregation was abolished upon treatment of the cells with a proteasomal inhibitor (MG132) [ 83 ].…”
Section: α-Synuclein: Folding Higher-order Structures and Degradamentioning
confidence: 99%
“…Knockout of DNAJB6 in HEK239 cells resulted in increased aggregation of α-synuclein [ 83 ]. Interestingly, this induced aggregation was abolished upon treatment of the cells with a proteasomal inhibitor (MG132) [ 83 ].…”
Section: α-Synuclein: Folding Higher-order Structures and Degradamentioning
confidence: 99%
“…We have previously shown that α-syn PFF seeded α-syn aggregation was increased in a HEK293 cell line, stably expressing α-syn-CFP and α-syn-YFP (hereafter named α-syn FRET cells), when DNAJB6 was knocked out (20). Here, we examined if overexpression of DNAJB6 would suppress α-syn aggregation induced by PFF's in the same cell line set up, and observed that overexpression of DNAJB6 decreased the seeded α-syn aggregation more than 4-fold ( Figure 1A and B).…”
Section: Overexpression Of Dnajb6 Is Protect Against α-Syn Aggregatiomentioning
confidence: 99%